Growth of Spirulina platensis Cultured with Inorganic Fertilizer (Urea, TSP and ZA) and Chicken Manure - N.B.P Utomo; . Winarti; A. Erlina (Jurnal Akuakultur Indonesia)
This experiment was conducted to compare the effectiveness of inorganic fertilizer and chicken manure on population growth and nutrient content of Spirulina platensis. It was found that Spirulina platensis cultured in inorganic medium reached a maximum population on day-9 with a density of 614.77x103 Sin/ml, containing 56.39% of crude protein and 17.92% of lipid. On the other hand, Spirulina platensis cultured in 250 ppm of chicken manure reached a maximum population on day-4 with a density of 434.32x103 Sin/ml, containing 45.39% of crude protein and 12.50% of lipid.